Stepping up the game: The role of innovation in the sharing economy - Vera Demary (Institut der deutschen Wirtschaft (IW), 2017)
While the sharing economy is generally perceived to be very innovative, it has hardly been analyzed what defines this innovativeness. The main aspect for the sharing economy as a whole is the peer-to-peer (P2P) organization of its businesses. This allows sharing platforms to enter markets more easily, consequently increasing com-petition in these markets. In addition to that, many sharing platforms are also techno-logically innovative or apply a tested concept in a new setting. Increased competition may result in even more innovation in order to keep customers satisfied and boost the benefit these derive from participating in the sharing economy. However, in most affected markets, there is no level playing field yet between the established incum-bents and the new sharing platform entrants. This calls for urgent action on the side of policy-makers to foster innovation in the sharing economy while enabling fair com-petition.
Keywords: L12; L51; L86; O31; 330